The Balanced Budget: Comment - Stein, Herbert (Quarterly Journal of Economics, 1955)
Journal Article The Balanced Budget: Comment Get access Herbert Stein Herbert Stein Committee for Economic Development, Washington 6, D. C. Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 69, Issue 1, February 1955, Pages 153–155, https://doi.org/10.2307/1884856 Published: 01 February 1955